The type of loose seton for complex anal fistula is essential to improve perianal comfort and quality of life. (8th June 2016) - Kristo, I.; Stift, A.; Staud, C.; Kainz, A.; Bachleitner‐Hofmann, T.; Chitsabesan, P.; Riss, S.
Abstract: Aim: The use of a loose seton for complex anal fistulae can cause perianal discomfort and reduced quality of life. The aim of this study was to assess the impact of the novel knot‐free Comfort Drain on quality of life, perianal comfort and faecal continence compared to conventional loose setons. Method: Forty‐four patients treated for complex anal fistula at a single institution between July 2013 and September 2014 were included in the study. A matched‐pair analysis was performed to compare patients with a knot‐free Comfort Drain and controls who were managed by conventional knotted setons. The 12‐item Short Form survey (SF‐12) questionnaire was used to assess quality of life. Additionally, patients reported perianal comfort and faecal incontinence using a Visual Analog Scale (VAS) and the St Mark's Incontinence Score. Results: The Comfort Drain was associated with improved quality of life with significant higher median physical ( P = 0.001) and mental ( P = 0.04) health scores compared with a conventional loose seton. According to the VAS, patients with a Comfort Drain in situ reported greater perianal comfort with significantly less burning sensation ( P < 0.001) and pruritus ( P < 0.001). Faecal continence was similar in each group. Conclusion: The Comfort Drain offers improved perianal comfort and better quality of life compared with a conventional loose seton and therefore facilitates long‐term therapy in patients with complex fistula‐in‐ano.